2007
DOI: 10.1016/j.bbamem.2007.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating healthy from tumor and necrosis tissue in rat brain tissue samples by Raman spectral imaging

Abstract: The purpose of this study was to investigate molecular changes associated with glioma tissues by Raman microspectroscopy in order to develop its use in clinical practice. Spectroscopic markers obtained from C6 glioma tissues were compared to conventional histological and histochemical techniques. Cholesterol and phospholipid contents were highest in corpus callosum and decreased gradually towards the cortex surface as well as in the tumor. Two different necrotic areas have been identified: a fully necrotic zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 41 publications
9
64
0
Order By: Relevance
“…These clusters were associated to the proliferative and invasive character of glioma tumors. In fact, in our previous study, immunohistochemical Ki-67 and MT1-MMP staining were used to visualize the proliferative and invasive activities of glioma and were clearly correlated with the cluster that encoded the surrounding tumor area (Amharref et al, 2007). Histopathological staining confirms this FTIR result ( fig.…”
Section: Ftir Characterization Of Normal Brain Tissues and C6 Glioma supporting
confidence: 60%
“…These clusters were associated to the proliferative and invasive character of glioma tumors. In fact, in our previous study, immunohistochemical Ki-67 and MT1-MMP staining were used to visualize the proliferative and invasive activities of glioma and were clearly correlated with the cluster that encoded the surrounding tumor area (Amharref et al, 2007). Histopathological staining confirms this FTIR result ( fig.…”
Section: Ftir Characterization Of Normal Brain Tissues and C6 Glioma supporting
confidence: 60%
“…15 These early studies provided the impetus for further research on human biopsy samples which are described in the next section. Animal models were also used to study normal and necrotic brain tissues by Amharref et al 17 Raman microspectroscopy of 15-m-thick brain sections followed by pseudo color maps were compared with histopathology and biomarkers for Ki-67 and MT1-MMP.…”
Section: Raman Spectroscopy-based Exploration In Brain Cancersmentioning
confidence: 99%
“…The rat glioma model has similar morphology to glioblastoma multiforme. 49 This study showed that Raman spectral features could be used to differentiate tumor, edema, necrotic, and healthy brain tissue. Specific spectral bands associated with proteins and lipids are the main Raman spectral features used for differentiation.…”
Section: Raman Spectroscopymentioning
confidence: 85%